A CRITICAL STUDY OF THE INFLUENCE OF THE FAMILY ENVIRONMENT AND SOCIAL AND ECONOMIC STATUS ON THE PERSONALITY OF BOYS AND GIRLS - Sharma, Himadri; Bhatnagar, Shivani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Adolescence, also known as the spring season, is the most important stage of human life among the four main stages, which is also considered to be the basis for personality development of boys and girls. All types of mental powers, emotions and imagination develop rapidly in humans at this stage, which becomes the identity of human personality. Although, in the development of a child's personality, the thinking, education, ideals, values ​​of their parents, their behavioural, economic, social environment, their values, their interpersonal relationship with the child, their personality traits, their emotional, social behaviour, likes-dislikes and character, their duties etc. all play an important role, but the two most important factors among these are the child's family environment and his socio-economic status, which are the foundation of his personality. Because a positive family environment and good socio-economic status make adolescents satisfied, social, value-oriented, idealistic, whereas a negative family environment develops negative qualities in adolescents. The presented research paper is a review paper in which an attempt has been made to understand the influence of family environment and socio-economic status on the personality of boys and girls by using a well-planned and systematic review method.